2022
DOI: 10.3390/cells11040597
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aging Effects of a Serum Based on Coconut Oil Combined with Deer Antler Stem Cell Extract on a Mouse Model of Skin Aging

Abstract: Anti-aging is one of the top goals in the field of health care and aesthetics. Anti-aging cosmetics derived from nature are oriented to long-term development, bringing safety to users and being environmentally friendly. The aim of this study was to develop an anti-aging cosmetic formulation process based on coconut oil in combination with deer antler stem cell extract. The results show that the presence of deer antler stem cell extract added to the foundation made the serum product highly stable and helped imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The skin is the largest organ in the human body, and serves as a critical protective mechanical, chemical, immune, and biological barrier against the environment. 6 The SC, the outermost layer of the epidermis, forms the main barrier and is composed of non-living corneocytes and a mixture of lipids organized in bilayers. 7 Epidermal sebum is composed of sebum secreted by the sebaceous glands and epidermal lipids produced by disintegrating SC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The skin is the largest organ in the human body, and serves as a critical protective mechanical, chemical, immune, and biological barrier against the environment. 6 The SC, the outermost layer of the epidermis, forms the main barrier and is composed of non-living corneocytes and a mixture of lipids organized in bilayers. 7 Epidermal sebum is composed of sebum secreted by the sebaceous glands and epidermal lipids produced by disintegrating SC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The pilose antlers are a valuable traditional Chinese medicine. Studies have shown that pilose antlers have anti-inflammatory, anti-fatigue, antioxidant and anti-osteoporosis effects and can enhance immunity ( Zha et al, 2013 ; Ma et al, 2017 ; Pham et al, 2022 ; Pei et al, 2023 ). Therefore, the primary purpose of raising deer is to produce pilose antlers.…”
Section: Introductionmentioning
confidence: 99%
“…An emollient is an ingredient used in skin care formulations that helps in maintaining the softness and smoothness of the skin and contributes to the moisturizing, lubricating, and conditioning effects which formed semi-occlusive films on the skin (Lodén & Maibach, 2012;Purnamawati et al, 2017;Chao et al, 2018;Pham et al, 2022). In clinical practice, it helps to reduce the itching sensation often present in dry skin while improving the appearance of the stratum corneum (Perrett & Peters, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Emollients may decrease the friction coefficient due to their lubricant properties and modify the spreading performance of the product (Savary et al, 2013). Emolliency is the softening ability that is one of the most important parameters in skin moisturization as emollient helps to balance the skin moisture (Lodén & Maibach, 2012;Pham et al, 2022).…”
Section: Introductionmentioning
confidence: 99%